Dual properties of PEGDA-GelMA scaffold: good long-term cerebral biocompatibility but limited potential for brain regeneration - Maylis Combeau; Vincent Lanternier; Adrien Brilhault; Julien Clauzel; Lorenne Robert; Nina Colitti; Melissa Parny; Carla Cirillo; Isabelle Raymond-Letron; Franck Desmoulin; Isabelle Loubinoux (Stem Cell Research & Therapy, 2026)
Abstract Background Acute brain injuries pose a significant clinical challenge, as current therapeutic strategies are insufficient to promote tissue regeneration or fully restore lost neurological functions. In this context, biomaterials have shown promise in promoting tissue repair. Methods This study introduces an innovative strategy involving the 3D Digital Light Processing (DLP) printing of a degradable scaffold composed of polyethylene-glycol diacrylate (PEGDA) and gelatin methacryloyl (GelMA). The neuro-implant combines the mechanical stability of PEGDA with the bioactivity and biocompatibility of gelatin, forming a porous, guiding architecture. This scaffold was implanted in rat brains injured by malonate injection. Results DLP technology enabled the creation of a complex scaffold architecture tailored to cortical anatomy. Longitudinal follow-up using behavioral assays and MRI and fMRI at 1-, 3-, and 6-months post-injury revealed a favorable in vivo safety profile, perilesional and contralesional functional MR activation, and a trend toward improved grip strength in the impaired forelimb at 6 months (p = 0.057). MRI provided high-quality images revealing the scaffold’s fine architecture in vivo and showed no major degradation. Histological analysis on small samples confirmed chronic biocompatibility, with complete colonization by viable endogenous cells, including a stable vascular network persisting at 6 months; a high density of neural progenitors (Sox2⁺, Dcx⁺ and beta-III tubulin⁺); and mature oligodendrocytes (Osp⁺). However, there was no evidence of mature, functional neurons or GFAP + astrocytes. Conclusion The PEGDA–GelMA scaffold demonstrates long-term biocompatibility in the brain but limited functional regenerative potential. Nevertheless, it might contribute to improve functional motor outcome. This potential improvement cannot be explained by neuron or astrocyte attraction. As an acellular implant, PEGDA–GelMA acts as a structural bridge between healthy and damaged brain tissue, attracting endogenous cells and stabilizing lesion sites, which may enhance brain plasticity mechanisms. These findings provide an acellular foundation for developing a regenerative, brain-compatible structural platform targeting central nervous system lesions.